Just a heartbeat away - Bastone, Cara (Bastone, Cara, Forever yours, 2020)
Newly widowed dad Sebastian Dorner was unraveling at the edges--until his son's teacher, Via DeRosa, threw him a lifeline. Now, two years later, they reconnect at Matty's new school, and an inconvenient but unmistakable jolt of attraction crackles between them. But why does the first person to spark with Sebastian in years have to be a millennial? Is twentysomething Via really too young for him or does fortysomething Sebastian just feel too damn old? A former foster kid, Via's finally forged the stable life she's always dreamed of--new job, steady income, no drama. The last thing she needs are rumors about her and a single dad at school. But why does she keep being drawn into his capable, worn-flannel orbit? And why does being around Sebastian, Matty and even their dog, Crabby, seem to spark so much want? They're trying to ignore the tension threatening their friendship. But sometimes what'll heal you is just a touch--and a heartbeat -- away.--Page 4 of cover